Marketing Approach to Environmental and Economic Assessment of National Development - DANKO, T. P.; KISELEV, V. M.; CHAYKOVSKAYA, L. A.; SEIFULLAEVA, M. E.; TULTAEV, T. A.; RAUSKIENE, Ona; SEKERIN, Vladimir D. (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020DO - 10.14505//jemt.11.5(45).14, 2020)
The main growth factor for a developing economy is the implementation of investment projects by economic subjects pursuing the objectives of increasing productivity and labour engagement, modernisation and development, production risk mitigation and increasing investment attractiveness, all aligned with the green technology context. Green technologies are a relatively new instrument of economic development. The purpose of this paper is to assess the environmental and economic security and sustainability of regional socioeconomic systems with an emphasis on establishing the relation between the innovative and environmental components of their development. Economic security and sustainable development of regional socioeconomic systems depend on a significantly wide range of factors of a balanced approach to regional development potential and its operation.